Recognition and enforcement of foreign judgments outside the scope of the Brussels and Lugano Conventions = Reconnaissance et exécution des jugements etrangers hors des conventions de Bruxelles et de Lugano /: Reconnaissance et exécution des jugements etrangers hors des conventions de Bruxelles et de Lugano. (2000) - Unknown
No abstract available